2020
DOI: 10.3389/fpls.2019.01683
|View full text |Cite
|
Sign up to set email alerts
|

NtMYB12 Positively Regulates Flavonol Biosynthesis and Enhances Tolerance to Low Pi Stress in Nicotiana tabacum

Abstract: Phosphorus (P) is an essential macronutrient for plant growth and development. The concentration of flavonol, a natural plant antioxidant, is closely related to phosphorus nutritional status. However, the regulatory networks of flavonol biosynthesis under low Pi stress are still unclear. In this study, we identified a PFG-type MYB gene, NtMYB12, whose expression was significantly up-regulated under low Pi conditions. Overexpression of NtMYB12 dramatically increased flavonol concentration and the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 62 publications
3
19
0
Order By: Relevance
“…6), which was supported by previous studies focusing LP in soybean [32,42]. Previous research showed that NtMYB12 acts as a phosphorus starvation response enhancement factor and regulates NtCHS and NtPT2 expression, which results in increased avonol and P accumulation and enhances tolerance to LP stress [43]. In this study, targets of lncRNAs were enriched as KEGG pathway including avonoid, iso avonoid and phenylpropanoid biosynthesis, indicating that those lncRNAs may be involved in secondary metabolites to regulate P responsive genes, which needs further research.…”
Section: Discussionsupporting
confidence: 65%
“…6), which was supported by previous studies focusing LP in soybean [32,42]. Previous research showed that NtMYB12 acts as a phosphorus starvation response enhancement factor and regulates NtCHS and NtPT2 expression, which results in increased avonol and P accumulation and enhances tolerance to LP stress [43]. In this study, targets of lncRNAs were enriched as KEGG pathway including avonoid, iso avonoid and phenylpropanoid biosynthesis, indicating that those lncRNAs may be involved in secondary metabolites to regulate P responsive genes, which needs further research.…”
Section: Discussionsupporting
confidence: 65%
“…6), and these ndings are supported by previous studies focusing on LP in soybean [33,43]. Previous research has shown that NtMYB12 acts as a phosphorus starvation response enhancement factor and regulates NtCHS and NtPT2 expression, which results in increased avonol and P accumulation and enhances tolerance to LP stress [44]. In this study, targets of lncRNAs were enriched in various KEGG pathways, including avonoid, iso avonoid and phenylpropanoid biosynthesis, which indicates that these lncRNAs might be involved in the synthesis of secondary metabolites to regulate P-responsive genes, but this hypothesis needs further research.…”
Section: Discussionsupporting
confidence: 63%
“…Importantly, the beneficial effect of hp2 in stress tolerance may extend beyond heat stress due to the fact that flavonols play an important role in protecting against oxidative stress which accompanies many other environmental stresses such as cold, drought and nutrient starvation (Nakabayashi et al 2014;Song et al 2020;M. Zhao et al 2019;Zandalinas et al 2017).…”
Section: Discussionmentioning
confidence: 99%